THE ANALYSIS OF VIOLATION OF MAXIMS IN CONVERSATIONAL IMPLICATURE FOUND IN DJARUM 76 ADVERTISEMENTS JIN VERSION - I Luh Meiyana Ariss Susanti; Gede Hendri Setiawan (Indonesian Journal Of Educational Research and Review, 2019)
This study aimed to analyze the violation of maxims in conversational implicature found in djarum 76 advertisements “Jin Version” and find out the audiences understanding about the Djarum 76 Advertisements “Jin Version” with a violation of Grice maxims in their conversation, this study used qualitative descriptive method to find out the violation of Gricean maxims. And to know the effect of maxims violation in delivering the advertisements messages, the researcher spread the questionnaire to the society by taking 30 peoples as sample. From the result of violation analysis, there were four types of Grice maxims violated. And then from the result of questionnaire analysis, the researcher found out that the advertisement was attractive. Based on those data the researcher concluded that the audiences interest to watch the advertisements and they understand enough with the messages which was deliver by Djarum 76 “Jin Version” although there were Gricean maxims violations.